(untitled) (Research, Society and Development, 2023)
The objective of the present study was to investigate, through a systematic scientific review, information published in journals on the theme of using biofloc technology in young fish. We sought to examine qualitatively and quantitatively documents related to the subject adopted, collected in the Scopus and Web of Science databases, from 2015 to May 2023. It was understood that scientific works involving intensive technologies of production in order to reduce the use of water resources and land spaces necessary for the activity, can be worked on a larger experimental scale, through partnerships with companies and private properties, as they are denoted in research institutions abroad. In conclusion, although the subject is relatively recent in the field of scientific research, new research is proposed with partnerships and technical-scientific follow-up, which can be carried out based on the sustainable use of biofloc technology applied in an economic and social way in fish farming.